Job satisfaction among Nurses in a Hospital - Shrestha, G K; Singh, B (Journal of Nepal Health Research Council, 2011)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Background: Nursing is one of the stressful jobs in health sector. The level of job satisfaction in the profession remains a matter of concern. This study means to explore the job satisfaction among the nurses of Dhulikhel Hospital. Methods: A Descriptive cross sectional study design was conducted in Dhulikhel Hospital; a community based Hospital of Kathmandu University from January to December 2009. All the nursing staffs that consented to the study filled up a standard questionnaire. Results: A total of 85 nurses completed the study. The mean age of the respondentsâ€™ was 23. 80.6% of the nursing staffs were satisfied. â€œBeing considered a resource of healthâ€ provided highest sense of satisfaction, while â€œLack of opportunities for further education and trainingâ€ provided lowest sense of satisfaction. Conclusions: Majority of the nurses were satisfied with their present condition of work. Since job satisfaction is a dynamic process, the result may not be static or consistence. Working environment and employees expectations should receive attention. Key words: experiences, job satisfaction, level of education, nurse